PEMBUATAN APLIKASI MODIFIKASI ANDROID UNTUK KEGIATAN INVENTARISASI TEGAKAN SEBELUM PENEBANGAN DI HUTAN BUKIT DAMAR GUSANG KECAMATAN BATI-BATI - Nur Fauzan; Mufidah Asy'ari; Suyanto Suyanto (Jurnal Sylva Scienteae, 2020)
The Ministry of Environment and Forestry in 2016 re-issued the regulation P.60 / Menlhk / Setjen / Kum.1 / 2016 on article 23 point 1 in its contents "All stages of administering timber forest products from natural forests are carried out through SIPUHH. One of them is the use of android-based ITSP. Android smartphones are equipped with Global Positioning System, that is connected to satellites so they can capture coordinates without commercial networks. This study aims to modify the ITSP application and determine the level of time difference between manual recording and android recording. This study uses the Waterfall method, namely the stages of making an Android application and a comparative method to compare the time of use of Android and the manual for use in the forest. The results of this study are an Android-based ITSP application created on the Thunkabel App web and Android Thunkable emulator. The results of the comparison of the time tested on 10 trees were obtained when the average use of Android was 0.38 seconds while the manual was 0.26 seconds. Comparison of the time on the 5 plots of measurement obtained the average usage time of Android 3.00 seconds while the manual is 2.11 seconds. Factors that affect the use of Android for longer because the registrar with android are less accustomed. The advantages of using ITSP android in the form of coordinates of each tree is immediately obtained and the results of tree data that has been input stored in the CSV extension that can be opened with Microsoft Excel, while the ITSP deficiency manual tree data must be retyped to make a cruising report.Keywords: Android Aplication; Forest Inventore; Barcode